Effect of organic amendments in seed production of radish (Raphanus sativus) - THAKUR, KULDEEP S; YADAV, NITIN; BHARDWAJ, RAMESH K (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at the Vegetable Research Farm, Department of Vegetable Science, Dr. Y S Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh during the rainy (kharif) season of 2019, 2020 and 2021 to evaluate the effect of different organic amendments in seed production of radish (Raphanus sativus L.) cv. Chinese Pink. The experiment was laid out in Randomized Block Design, consisting of seven treatments with three replications. The treatments were: T1, Control; T2, FYM @20 t/ha; T3, Vermicompost @8 t/ha; T4, FYM @10 t/ha + vermicompost @4 t/ha; T5, FYM @20 t/ha + Vermiwash @1:1 (v/v - water + vermiwash) spray; T6, Vermicompost @8 t/ha + Vermiwash @1:1 (v/v - water + vermiwash) spray; T7, FYM @10 t/ha + Vermicompost @4 t/ha + Vermiwash @1:1 (v/v – water + vermiwash) spray. Pooled data of three consecutive years revealed that application of T7 recorded maximum plant height (127.30 cm), number of branches per plant (9.89), highest number of pods per plant (690.57), more seed yield per plant (30.35 g) and seed yield per hectare (5.93 q). This treatment also resulted in maximum 1000-seed weight (11.83 g), germination (94.77%), seed vigour index-I (2420.51) and seed vigour index-II (669.33) along with highest net return (`458135.70/ha) and benefit:cost ratio (3.40).